2013
DOI: 10.3390/rs5052308
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Stand Height, Volume, and Biomass from Very High Spatial Resolution Satellite Imagery and Samples of Airborne LiDAR

Abstract: Abstract:Plot-based sampling with ground measurements or photography is typically used to establish and maintain National Forest Inventories (NFI). The re-measurement phase of the Canadian NFI is an opportunity to develop novel methods for the estimation of forest attributes such as stand height, crown closure, volume, and aboveground biomass (AGB) from satellite, rather than, airborne imagery. Based on panchromatic Very High Spatial Resolution (VHSR) images and Light Detection and Ranging (LiDAR) data acquire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 35 publications
2
31
0
2
Order By: Relevance
“…In terms of the forest stand variables to be predicted, most studies focused on the estimation of conventional forest stand variables such as SV, NT, BA, and QMD using remotely sensed data [35,55,74,75]. Only a few studies have investigated the extraction of the more complex structural variables such as tree size diversity and tree position diversity [13,76,77].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the forest stand variables to be predicted, most studies focused on the estimation of conventional forest stand variables such as SV, NT, BA, and QMD using remotely sensed data [35,55,74,75]. Only a few studies have investigated the extraction of the more complex structural variables such as tree size diversity and tree position diversity [13,76,77].…”
Section: Discussionmentioning
confidence: 99%
“…In Mora et al [25], only stand height was modeled, and RMSE accuracy of 2.3 m (21%) was obtained in British Columbia, Canada, using a k-nearest neighbor (k-NN) approach. Mora et al [26] obtained an RMSE accuracy of 1.95 m (11.6%) for stand height, 9.6 m 3 /ha (12.8%) for stand volume and 22.2 t/ha (15.8%) for AGB. In both of these studies, accuracies were reported at the stand level (mean size 9.6 ha in [26]).…”
Section: Introductionmentioning
confidence: 99%
“…3 m RMS-accuracy [22,23]. Recently, ALS has been used for calibration and validation of forest characteristic predictions using optical imagery [24][25][26]. Chen et al [24] tested integration of Landsat imagery and ALS to estimate tree height variables.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wulder and Seemann [22] used an empirical model to estimate airborne LiDAR-derived stand heights from Landsat5 TM data after delineating forest stands with an image segmentation. Mora et al [23,24] estimated LiDAR-based stand heights with high resolution satellite images (i.e., QuickBird-2, Worldview-1) using diverse regression techniques including linear regression, k-nearest neighbor, regression trees, and random forest. However, prior studies were generally carried out on non-rugged terrain with relatively analogous tree species composition, which makes it difficult to apply to mountainous forests in South Korea.…”
Section: Introductionmentioning
confidence: 99%